Bukti-bukti adanya Allah M. Mutawalli Asy-Sya rawi ; penerjemah, A. Aziz Salim Basyarahim ; penyunting, Juariah Muhammad - ASY-SYA RAWI, M.Mutawalli; Basyarahil, A. Aziz Salim; Muhammad, Juariyah (Gema Insani Press, 1994)
121 hlm. ; 18 cm.